Progressive technologies of forging large parts with responsible destination - Kalchenko, P. P.; Markov, O. E.; Aliiev, I. S.; Hrudkina, N. S.; Грудкіна, Н. С. (Baltija Publishing, 2022)
The technological features of forging the main types of forged pieces in the monograph, which are often manufactured on hydraulic presses with a shorter length of waste for plates were considered; the production of crankshafts with reversal of crank in the process of forging; the principal issues of developing technology for forging hollow spherical forged pieces were stated; many other technical processes of forging large forged pieces were described, taking into account the latest advances in inventions and new technological solutions. The technological processes, which were developed by technologists of the Bureau of Large Forged pieces, which were applied to the production conditions of the machine-building plant for the needs of heavy engineering in this monograph were used. The monograph can be used as a textbook for undergraduates and bachelors in relevant specialities.